Уран бүтээлийн арга, түүнтэй холбогдох зарим хүчин зүйлс: Artistic method and its some factors - Д., Галбаатар (Mongolian Studies, 2023)
The author analyzes the artistic method of the literary work. Method of the literary work can be divided into realistic and non-realistic types and system of methods according to author’s objective and basis of idea. Literary work can be identified by the tradition and innovation, the world view, the artistic style and the philosophical doctrine.